Green biosynthesized silver nanoparticles using ficus deltoidea leaf extract as antibacterial agent - Ismail, Ibrahirul Qamil; Nik Malek, Nik Ahmad Nizam; Sani, Nor Suriani; Mohammad Din, Shahrulnizahana; Asraf, Muhammad Hariz (Universiti Teknologi MARA (UiTM), 2023)
Hazardous and harmful reducing agents are often utilized in the silver nanoparticle (AgNP) synthesis method. Hence, various bioresources acting as reducing agents are being researched for a greener and safer AgNP synthesis. This study aimed to investigate the green synthesis of AgNP using local Ficus deltoidea (Mas Cotek) plant leaf extract. The plant leaf extract was analyzed for its total phenolic (TPC) and flavonoid contents (TFC), and the values were determined to be 24.37 ± 0.57 mg/g and 1118.91 ± 8.55 mg/g, respectively. The optimized values of the AgNP synthesis obtained were 0.6 ml F. deltoidea extract (5%) at pH 8 with the synthesis temperature at 80°C and 24 hours reaction period. The biosynthesized AgNP was characterized using UV-visible spectroscopy, showing a peak at around 440 nm to 450 nm. The Fourier transform infrared (FTIR) spectra of the AgNP and plant extract showed prominent peaks around 3400 cm-1, 1600 cm-1, and 1360 cm-1, corresponding to the functional groups in the plant extract. Transmission electron microscope (TEM) image showed that the AgNP was spherical, with sizes ranging from 10 nm to 50 nm. Antibacterial assays that were done based on disc diffusion technique (DDT) against Gram-positive (Staphylococcus aureus ATCC 6538), Gram-negative (Escherichia coli ATCC 11229), and anaerobic skin bacterium, Cutibacterium acnes ATCC 6919 present significant halo-zone formation. The biocompatibility of the sample against HSF1184 human fibroblast skin cells showed that the IC50 value of the biosynthesized AgNP (0.25 mg/ml) was lower than the commercial AgNP (1.0 mg/ml). This study showed that the phenolic and flavonoid contents in F. deltoidea leaf extract enable the synthesis of AgNP and exhibit antibacterial effects against Gram-positive, Gram-negative, and skin bacteria while presenting a mild cytotoxicity level against human fibroblast cells.